Formation and alloying of nanostructured β-W powders - Angastiniotis, Nicos; Kear, B.H.; McCandlish, L.E.; Ramanujachary, K.V.; Greenblatt, M. (My University, 1992)
We have been investigating the reductive decomposition of spray dried ammonium metatungstate (AMT). Reduction of the pyrolysed powder in flowing hydrogen at T ≥ 625° C creates α-W, with bcc structure. Reduction at T ≤ 575° C results in the formation of W3O, with A15 structure. In situ reduction experiments carried out in a controled atmosphere, high temperature X-ray powder diffractometer have shown that W3O transforms to β-W, in which most of the oxygen atoms are absent. Various experiments confirming the existence of WO1-x are described. Initial experiments on its alloying behavior with nitrogen are also discussed. © 1992.
Keywords: β-W powders; Αmmonium metatungstate (AMT); Formation